Peran Gamifikasi dalam Meningkatkan UX Aplikasi Shopee di Indonesia - Putra, I Kadek Permana; Pradnyana, I Made Ardwi; Saskara, Gede Arna Jude (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
The implementation of gamification on e-commerce platforms holds the potential to enhance user engagement and satisfaction. However, several studies indicate that the impact of gamification on User Experience (UX) can vary, with gamification elements sometimes only providing short-term effects or even being insignificant. This research aims to analyze how gamification influences the perception of User Experience (UX) among users of the Shopee Games feature in Indonesia. A simple linear regression method was employed in this study. Data collection was conducted through surveys distributed to Shopee Games users. Regression analysis revealed a significant relationship between gamification and UX, with a correlation coefficient (R) of 0.755, indicating a strong relationship. The R Square value of 0.571 confirms that 57.1% of the variance in UX can be explained by gamification. The results of the ANOVA test reinforce these findings with a significance value of < 0.001, proving that the regression model used is valid and that gamification has a statistically significant impact on UX. Furthermore, further analysis found no issues of heteroscedasticity, thus fulfilling the classical regression assumptions. The implications of this research affirm that the effective implementation of gamification elements enhances users' perception of their experience when using the Shopee application. These findings recommend that e-commerce companies further optimize their gamification strategies to increase user engagement.